SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN INVESTASI IDEAL BAGI GENERASI MILLENIAL - Ruhul Amin; Bakhtiar Rifai (Jurnal Mantik Penusa)
The development of information system applications in Indonesia is currently experiencing rapid progress. The Indonesian community downloads and uses information system for investment, work, communication, shopping and many other activitie the other. It is estimated by experts for the future use of system  increased. The existence of investment in Indonesia is now growing, this is caused by the desire of the community to benefit in the future will com]. The lack of knowledge about investments owned by the community, the many criteria and alternatives in choosing investment will be a problem alone in an effort to choose the most ideal investment [2]. Decision support system built to help humans to help solve problems no structured and semi structured. Decision support information system development investment selection has the aim of helping the community or investors to choose the most appropriate and correct investment based on various criteria and alternatives predetermined to select various investments Stages of application development (1) needs analysis, (2) Design, (3) system implementation, (4) Support operations and (5) Evaluate Performance. Criteria and alternatives used in investment selection derived from prior research conducted by the author. Criteria consist of market risk liquidity, inflation, time period, investment value, return, income, while the alternative of investment are deposits, insurance, gold, shares, DPLK and mutual fund.